Lobsters: the search for knowledge continues (and why we need to know!) - Phillips, Bruce (New Zealand Govt, 2005)
Lobsters are the focus of very valuable fisheries, and mainly because of this are among the most researched animals on earth. There is a continuing and expanding need for their further study because of changing areas of public interest in their biology and management. They are used as animals for teaching students in a wide range of disciplines, and are species of considerable community interest. The range of scientific studies of lobsters includes: larval ecology, juveniles, behaviour, genetics, stocks, fishing gear and effects of fishing, recreational fishing, disease, post-harvest practices, economics, triple bottom line reporting, aquaculture and enhancement, eco-labelling and certification, ecosystem management, and marine protected areas. Examination of important research questions identified at workshops held at previous lobster conferences indicates that some of these questions are being addressed, but in many instances new priorities for research have occurred because of developing technologyin the fishery, increasing recreational fishing, disease, changing catch levels; as well as political developments such as marine protected areas, and changing and continuous demand for new or expanded data sets to address new issues such as eco-labelling. Dissemination of information about lobsters to a wide audience has resulted in a rangeof methods to achieve better communication including scientific papers, popular magazine articles, fishing magazine articles, and scientific and popular books and films.